Diagnostic of Students' Difficulties in Solving Mathematics Problems of National Examination Year 2015/2016 - Amin, Ahmad Kholiqul (Muhammadiyah University Press, 2017)
This research aims at ascertaining kinds of students' difficulties and factors causing students' difficulties in solving mathematics problems of national examination towards students grade IX MTs Darul Huda Year 2015/2016. This research is a qualitative descriptive research. The research subjects were 6 students grade IX of MTs Darul Huda Sugihwaras having difficulties in solving problems in mathematics. The technique of collecting samples in this research was conducted by purposive sampling technique. The subjects were chosen based on data provided by a mathematics teacher of grade IX and tryout result. The methods of collecting data which were applied were essay test, interview, documentation, and questionnaire. The data analysis was conducted by quantitative and qualitative analysis. The result shows that, (1) kinds of difficulties encountered by students are (a) Difficulty in understanding problems is 20%, with an indicator that students misunderstand the problems. The cause is the low basic concept of mastery;(b) Difficulty in applying formula is 36.67%, with an indicator that students make mistakes in applying formula. The cause is students do not recognize formula which must be applied in solving problems, students do not know formula which must be used. (c) Difficulty in solving problems is 30%, with an indicator that students make mistakes when solving problems. The cause is students do not know steps in solving problems. (d) Difficulty in drawing conclusion is 15%, with an indicator that students make mistakes due to carelessness in solving problems. The cause is students are slipshod in understanding problems and in remembering formula. The factor causing students' difficulties is the low students' interest towards mathematics since media/props provided by teachers are not applied optimally yet.